Expectancy Reduces Symptoms but not Functional Impairment Following Exercise-induced Musculoskeletal Injury. Issue 1 (January 2018) - Hedderson, William C.; Dover, Geoffrey C.; George, Steven Z.; Crow, Joshua A.; Borsa, Paul A.
Abstract : Objectives: To quantify the extent to which the participant-provider interaction influences the response to sham treatment following exercised-induced acute musculoskeletal pain. Materials and Methods: In total, 40 participants between the ages of 18 and 35 volunteered for the study. Participants came to the laboratory for 3 test sessions 48-hour apart (day 1, 3, and 5). During the initial session, baseline measures were assessed and participants underwent a fatigue protocol for the biceps brachii. Participants were then assigned to a positive expectation or a no-expectation condition before receiving a sham laser therapy treatment. The positive expectation group received symptom improvement priming before their sham treatment. Participants allocated to the no-expectation condition received no feedback before the sham treatment. Maximum voluntary isometric contraction; relaxed elbow angle; visual analog scale; and the QuickDash questionnaire were used as outcome measures. Results: The positive expectation group had a significant reduction in perceived pain compared with the no-expectation group at day 3 follow-up, with the mean scores being 34.65 mm (SE=4.44) compared with 49.4 mm (SE=5.79), respectively. There were no between-group differences with respect to maximum voluntary isometric contraction, QuickDash, or relaxed elbow angle outcomes. In addition, there were no significant between-group differences observed with expected pain on follow-up visits, the effect sizes were d =0.26 on day 1 for day 3 and d =0.51 on day for day 5. Discussion: Positive expectations before a sham treatment enhanced reduction in pain intensity but did not improve functional impairments following exercise-induced acute musculoskeletal injury.